«Iis, qui vix usquam locum tutum inveniunt». Giuristi, riformatori religiosi, fuorusciti. Matteo Gribaldi Mofa († 1564) - Diego Quaglioni (Laboratoire Italien)
Retracing the life of Italian jurist Matteo Gribaldi Mofa, who was exiled in Geneva for religious reasons, the author aims at showing how political, scientific and religious aspects are intermingled in the intellectual life of the large community of Italian exiles in Europe, at the end of the 16th century. The message of Gribaldi Mofa stating that no one should be condemned for his religious ideas and opinions has become a reference for personalities such as Jean Bodin, who has cited him to defend the ideal of freedom of conscience.